The Effectiveness of Picture in Improving Students’ Vocabulary Mastery Skills at the Fifth Grade Students - Hidayatulloh, Muh Taufiq; Amrullah; Lail, Husnul; Arifuddin (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This study investigated the effectiveness of picture media in improving English vocabulary mastery among fifth grade students at SDN 1 SUKAREMA. This study was a quasi-experimental study with a Nonequivalent Control Group Design. The sample of this study consisted of 60 students divided into experimental and control groups (n=30 each). The experimental group received instruction through picture media, while the control group used puzzle-based learning. Data were collected through pre-test and post-test assessments using 25 multiple-choice questions. The data analysis technique used prerequisite tests (normality test and homogeneity test) and hypothesis testing (t-test, independent sample t-test). The results showed significantly higher performance in the experimental group (M=86.40) compared to the control group (M=64.40). Independent Sample T-test analysis revealed a significant difference between the groups (p<0.05), with a mean difference of 22,000 and a variance ratio of 0.81. These findings indicate that the use of pictures is effective in improving students' vocabulary mastery skills in fifth grade students at SDN 1 SUKAREMA.